Addressing the altitudinal and geographical gradient in European beech via photosynthetic parameters: a case study on Calabrian beech transplanted to Denmark - Provazník, Daniel; Stejskal, Jan; Hansen, Ole Kim; Čepl, Jaroslav; Erichsen, Eva Roland; Hansen, Jon Kehlet; Zádrapová, Dagmar; Tomášková, Ivana (Frontiers in Forests and Global Change, 2024)
European beech (Fagus sylvatica L.) is becoming one of the go-to species in reconstructing declining conifer stands in Europe under climate change. Assisted migration may be considered when looking for suitable beech seedlings. Knowledge about the photosynthetic performance of beech seedlings is fundamental to understanding an essential part of their growth and survival potential in different planting conditions. We investigated the within-provenance variation in photosynthetic performance driven by altitude in contrast to inter-provenance variation given by geographical distance. The experiment was conducted on seedlings replanted in a Danish common garden comprising a cluster of provenances with various altitudinal subgroups transplanted from the Calabria region (Italy) and two local Danish provenances. Provenance and within-provenance variation in chlorophyll fluorescence (ChlF) kinetics, gas exchange (GE), flushing, and senescence were assessed. ChlF measurements revealed within-provenance differences based on altitude of origin and could distinguish between the two Danish provenances. In contrast, GE parameters detected variation in the geographical distance among Italian provenances. High-elevation subgroups of Italian provenances showed the best leaf-level photosynthetic performance in Danish weather conditions with high precipitation levels. Altitude of origin can be a significant source of within-provenance variation. We demonstrated that assessing this variation in young trees may be instrumental in maximizing the potential of provenance variation across diverse planting sites.